Analysis of Safety Shoes Product Quality Control at PT. BINA USAHA SEJAHTERA With Statistical Quality Control (SQC) Method Case Study of PT Bina Usaha Sejahtera (BINUSA) - Winata, Eko Fandra; Sugiyono, Sugiyono (Indonesian Journal of Business Analytics, 2024)
PT. Bina Usaha Sejahtera faces several problems that often occur, especially in increasing the number of Reject goods. The purpose of this study is to analyze the main causes of rejected goods in the production of Safety Shoes and to evaluate and analyze the application of the Statistical Quality Control (SQC) method and 7 quality control tools in overcoming the lack of rejected goods In addition, this study also aims to propose corrective actions and improve the quality of Safety Shoes products at PT Binusa using the 5W + 1H method. The sample population of this study is the result of data collection using check sheets for Safety Shoes during 2023, starting from January to October 2023. The requirement for the percentage of defective products in one year is less than 5% of the total production of the Binusa company. The sample used for research type BRG 0701 S1P amounted to 1,596 pcs.. SQC has succeeded in reducing the deviation rate from 6% to 1%.PT Bina Usaha Sejahtera has committed to encouraging a culture of quality excellence by streamlining the production process, providing regular training, and managing the production process in a structured manner.